2020
DOI: 10.1111/jcpp.13317
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Perspective: A plea for the sustained implementation of digital interventions for young people with mental health problems in the light of the COVID‐19 pandemic

Abstract: The coronavirus disease 2019 pandemic and the consequent global lockdown posed a particular challenge for youths with mental health problems. Crucial interference with their everyday lives likely increased psychological distress while accessibility of conventional mental health care was limited. Ongoing online trials offer a unique opportunity to analyse mental health status and help‐seeking behaviour of adolescents during the pandemic. The ProHEAD‐online trial aims at improving help‐seeking behaviour of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…While our data do appear comforting, they do not implicate that there is no need to support children and adolescents in a pandemic situation. Previously, we have described an increase in the utilization of the ProHEAD online interventions during the lockdown period in March 2020 [ 30 ]. Further, although our methodology allowed us to capture potential immediate effects of school-closings, it is well possible that actual effects on mental health are observed in longer follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…While our data do appear comforting, they do not implicate that there is no need to support children and adolescents in a pandemic situation. Previously, we have described an increase in the utilization of the ProHEAD online interventions during the lockdown period in March 2020 [ 30 ]. Further, although our methodology allowed us to capture potential immediate effects of school-closings, it is well possible that actual effects on mental health are observed in longer follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, positive attitudes toward the use of mHealth apps to help alleviate the psychosocial consequences of the pandemic were highly prevalent and associated with an objective need (e.g., more severe levels of psychological distress and higher levels of worrying). There have been also other studies which have reported that individuals have a positive attitude toward, and increasingly use, digital interventions during the current COVID-19 pandemic across the whole spectrum of public mental health provision (i.e., mental health promotion, prevention, and treatment of mental disorders) [36][37][38]49,50], and alterations of telemedicine regulations have been reported [51]. However, mHealth apps provide the opportunity of delivering lowthreshold, personalized mental health care in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, there has been a rapid increase in the use of online and digital mental health services and interventions, with promising and, in some cases, long-lasting effects on reductions of mental health problems 63 , with therapeutic effects similar to that of face-to-face therapies 64 . The COVID-19 pandemic, inevitably, led to a massive increase in the use of prescribed online interventions and therapy programs [65][66][67] . Rauschenberg and colleagues 68 reviewed 83 studies on the feasibility, use, and benefits of online interventions for mental health concerns in the general population during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Several countries reported a massive increase in the use of psychological crisis helplines across all ages, with a particular high need among young adults (e.g., [72][73][74][75] ). Hence, with a (increasing) deterioration in people's mental wellbeing during the pandemic, more people are now seeking help through digital services [65][66][67] . However, as shown by one exemplary survey, only about 8% of the adults in the UK use available online services to directly support their mental health during COVID-19 76 .…”
Section: Discussionmentioning
confidence: 99%